The Pacification of Peru and the Production of a Neoliberal Populist Order. (1st April 2017) - Maritza Felices Luna
Abstract : This article analyses the security, governance and economic reforms carried out by Fujimori in the 1990s as strategies of pacification seeking to restore a capitalist social order disturbed by the economic and social turmoil of the 1970s and 1980s. First, I show how different forms of state violence were intrinsically connected to the pacification process. Then, I argue that the social order produced resulted from the articulation of populism and authoritarianism with neoliberalism. Subsequently, I contend that crimes, harms and violence continue within the current democratic configuration precisely because pacification is an ongoing process seeking to maintain an order which is intrinsically exploitative, creates favourable conditions for economic crimes and corruption and resorts to repressive violence when challenged. I conclude by suggesting that the social, political and economic landscapes that provided the impetus for pacification have been transformed through the new social order, further weakening already frail democratic institutions.